Analisis Permasalahan Optimalisasi Voice CDMA 2000 1x Untuk Mengurangi Kegagalan Koneksi Studi Kasus Divisi Telkom Flexi Semarang - Alfin Hikmaturokhman; Eka Wahyudi; Septy Widya Pangestika (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2011)
Rapidly growing number of network providers in Code Division Multiple Access (CDMA), make service providers to further strength its network and optimization customer service and quality that will be given. In order to better serve our customer with the required network that has good performance. For that we need to be optimization in network, which can reduce the drop call and resource blocking and increasing call success. Network optimization is based on data drive test as for data analysis, including Call Setup Success Rate, Drop call Rate, Resource Blocking, Rx Power, Tx Power, Ec/Io, Forward FER, and Call Setup Time. In the measurement that have been done to the avarage value in accordance with Key Performance Indicator (KPI) obtained Call Setup Success Rate (> 99%), Drop call Rate (< 2%), Resource Blocking (< 2%), Rx Power (-91.7 dBm), Tx Power (11.4 dBm), Ec/Io (-21.38 dB), Forward FER (4.8%), and Call Setup Time (4.832 seconds). Result the performance of the Flexi network for service in Jepara #2 area in poor condition, because for parameters Rx Power, Tx Power, Forward FER, and Ec/Io not suitable with KPI. So do the optimization for the better network quality. Result after optimization of average Call Setup Success Rate (> 99%), Drop call Rate (< 1%), Resource Blocking (< 1%), Rx Power (-99.9 dBm), Tx Power (-27.8 dBm), Ec/Io (-5.45 dB), Forward FER (2.45%), and Call Setup Time (4.902 seconds).